Efektivitas Strategi Digital Marketing dalam Meningkatkan Penjualan Paket Umroh PT Masitoh Travel Qolbi Medan - Putri Mesyha Khairani; Abi Waqqosh (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to determine the effectiveness of digital marketing strategies in increasing sales of PT Masitoh Travel Qolbi Medan Umrah packages. The research used is qualitative. Qualitative research is a research process based on a methodology that investigates a social phenomenon and social problem, namely by creating a complex picture, including words, detailed reports from the respondent's views. The research method used is the case study method, namely research carried out by looking directly at the field. Case study is a method that explains the type of research regarding a particular object over a period of time, or a phenomenon that is determined in a place that is not necessarily the same as other research areas. The results of this research show that PT Masitoh Travel Qolbi Medan has implemented digital marketing in its Umrah marketing, but the application of digital marketing at PT Masitoh Travel Qolbi Medan in Umrah marketing is by utilizing TikToks, and social media such as Instagram, Facebook as the main support (supporting system) so that can reach a wider market, it is still considered less effective compared to marketing through the influence of the owner. With the owner's background as a religious teacher or lecturer, marketing through the owner's influence is considered more effective because many of the congregation who know PT Masitoh Travel Qolbi Medan, carry out Umrah pilgrimage trips and register at PT Masitoh Travel Qolbi Medan are the congregation who took part in the study from the PT Owner Masitoh Travel Qolbi Medan.